2014
DOI: 10.1074/jbc.m113.525014
|View full text |Cite|
|
Sign up to set email alerts
|

Blockade of Fas Signaling in Breast Cancer Cells Suppresses Tumor Growth and Metastasis via Disruption of Fas Signaling-initiated Cancer-related Inflammation

Abstract: Background:The non-apoptotic functions of Fas signaling have been proposed to play an important role in promoting tumor progression. Results: Blockade of Fas signaling suppresses tumor growth and metastasis via disruption of Fas signaling-initiated cancerrelated inflammation. Conclusion: Fas signaling-initiated cancer-related inflammation in breast cancer cells may be a potential target for cancer treatment.Significance: This study provides mechanistic insight into the role of Fas signaling in cancer-related i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 50 publications
3
18
0
Order By: Relevance
“…However, the thresholds vary between 50 and 60 % stromal lymphocytes leucocyte numbers [66] and NK cells [67] as well as decreased IFN-γ production and STAT1 signalling [45]. Furthermore, in CD8 + CTLs isolated from blood samples of breast cancer patients, significant upregulation of FAS [57,58,68] as well as significant downregulation of the T cell receptor (TCR), responsible for antigen recognition and its co-receptor CD28, have been observed [42]. Moreover, numerous studies have shown upregulation in FoxP3 + Tregs [69, 70•, 71] and MDSCs [45,[72][73][74] as well as elevated arginase [75,76], dampening immunity in breast cancer through suppressive actions on CTLs, DCs and NK cells [76,77].…”
Section: Mechanisms Of Immunity Generation and Suppression In Breast mentioning
confidence: 96%
See 2 more Smart Citations
“…However, the thresholds vary between 50 and 60 % stromal lymphocytes leucocyte numbers [66] and NK cells [67] as well as decreased IFN-γ production and STAT1 signalling [45]. Furthermore, in CD8 + CTLs isolated from blood samples of breast cancer patients, significant upregulation of FAS [57,58,68] as well as significant downregulation of the T cell receptor (TCR), responsible for antigen recognition and its co-receptor CD28, have been observed [42]. Moreover, numerous studies have shown upregulation in FoxP3 + Tregs [69, 70•, 71] and MDSCs [45,[72][73][74] as well as elevated arginase [75,76], dampening immunity in breast cancer through suppressive actions on CTLs, DCs and NK cells [76,77].…”
Section: Mechanisms Of Immunity Generation and Suppression In Breast mentioning
confidence: 96%
“…As a result, tumour cells become more susceptible to NK cell-mediated cytolytic activity [55]. Tumour-mediated deletion of immune effector populations is another mechanism used to hinder antitumour immunity in breast cancer [57]. The Fas (CD95, Apo-1)/Fas ligand (Fas-L) apoptotic pathway is a key mediator of T cell deletion [57,58].…”
Section: Mechanisms Of Immunity Generation and Suppression In Breast mentioning
confidence: 99%
See 1 more Smart Citation
“…Epidemiological data has indicated that >25% of various types of cancer are associated with chronic infection and inflammation (29). It has been demonstrated that the administration of non-steroidal anti-inflammatory drugs is associated with a reduction in the risk of developing various types of cancer, including BC (33). A previous study identified that sPLA2 regulates the activation of Ras and extracellular signal-regulated kinase and induces the phosphorylation of the epidermal growth factor receptor via a protein kinase C-dependent pathway, which may lead to a poor patient prognosis in an inflammatory microenvironment (34).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in an orthotopic breast cancer model, the chemokine CCL2, was found to be a major chemoattractant for inflammatory monocytes, and was critical for the development of a metastatic niche in the lungs, but not for primary tumor development 43,44 . Blockade of Fas signaling, better known for its role in apoptosis, was recently demonstrated to reduce tumor size and metastatic burden in an orthotopic breast cancer model, by reducing tumor production of IL-6, which inhibited immature myeloid cell accumulation into tumors 45 . Taken together, inflammatory cytokines and chemokines produced by cancer cells can attract immature myeloid cells or pro-inflammatory T-helper cells into tumors, creating a pro-tumorigenic microenvironment, stimulating cancer cell growth.…”
Section: Introductionmentioning
confidence: 99%